Interface entre voz, linguagem, cognição, alteração de humor e bioespectroscopia no contexto clínico da esclerose múltipla - Santiago, Raí dos Santos (2023)
Introduction: Multiple sclerosis is a chronic disease affecting the central nervous system, characterized by inflammation, demyelination, and neurodegeneration. These lesions lead to dysfunctions in various functional systems, including speech, language, cognition, and the development of disorders such as anxiety and depression. Infrared spectroscopy has been investigated as a promising and clinically useful technique capable of representing both the onset and progression of the disease, enabling early identification. Objective: To conduct a multidisciplinary study in patients with MS, covering cognitive and functional aspects to systemic biochemical aspects in their biofluids. Method: This study included 52 patients diagnosed with MS and 52 control participants matched for gender, age, and education. A questionnaire was administered to collect sociodemographic and clinical data from volunteers, along with the following protocols: a) Vocal Handicap Index – 10; b) Vocal Fatigue Index; c) Voice Quality of Life; d) Verb Fluency; e) Addenbrooke’s Cognitive Examination – Revised; f) Beck Depression Inventory; g) Beck Anxiety Inventory; and h) Functional Communication Abilities Assessment. For bio-spectroscopy analysis, serum was obtained from capillary blood of the participants and analyzed using Fourier-transform infrared spectroscopy. Chemometric analyses were conducted on the entire spectrum (3700 - 900 cm-1 ) and separated into fingerprint regions (1800 - 900 cm-1 ) and high wavenumber regions (3700 - 2800 cm-1 ). Results: The MS patient group consisted of 35 women and 17 men, with a mean age of 39.5 ± 12.7 years. The control sample comprised 36 women and 16 men, with a mean age of 39.3 ± 12.4 years. We observed that the MS patient group showed poorer results in vocal assessment questionnaires compared to the control group. In cognitive evaluation, deficits were observed in various domains, except for episodic and semantic memory. In pragmatic assessment, impairments were found in all investigated domains except communicative interaction, where no difference was observed between the groups. Regarding the evaluation of anxiety and depression symptoms, the MS group scored significantly higher in the corresponding test battery. Using the FTIR method, differences in spectral fingerprint and high wave number regions, through multivariate analyses, indicate metabolic changes with an increase in the concentration of phospholipids/lipids, nucleic acids, and Amide I and II in the MS group. Conclusion: A significant impact on vocal quality in individuals with MS was identified, along with cognitive, pragmatic, anxiety, and depression impairments. Through the FTIR method, it was observed that the total spectrum provides significant information for group differentiation.